(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2019)
The particulate matter present in the atmospheric air of large cities is one of the pollutants that causes great environmental risks. Due to their composition of solids and liquids varying in size, shape, composition and origin, they have an impact on the health of the exposed population, agriculture, forests and acidification of lakes. In this scenario, the present work had as objective to evaluate the concentration of the 10-micrometer particulate matter, commonly called PM10, and the elementary concentrations in air filters whose sampling was carried out at the Campus of the Federal University of Minas Gerais. For this, a high-volume sampler was used to collect the particulate matter. The elementary concentration of the particulate matter was determined via neutron activation analysis, method k0. Applying the enrichment factor technique, the influence of anthropogenic sources at the sampled site was investigated. The results showed anthropogenic interferences of zinc, sodium, chromium and iron and a geogenic impoverishment of cobalt.